Chronic traumatic encephalopathy and risk of suicide in former athletes - Iverson, G. L. (British Journal of Sports Medicine, 2014)
Background: In the initial autopsy case studies of chronic traumatic encephalopathy (CTE), some researchers have concluded that the proteinopathy associated with CTE is the underlying cause of suicidality and completed suicide in former athletes. Methods: A review of the literature on contact sports and risk of completed suicide revealed only one epidemiological study with direct relevant data. Results: There are no published cross-sectional, epidemiological or prospective studies showing a relation between contact sports and risk of suicide. One published epidemiological study suggests that retired National Football League players have lower rates of death by suicide than the general population. Outside of sports, there is a mature body of evidence suggesting that the causes of suicide are complex, multifactorial and difficult to predict in individual cases. Conclusions: Future research might establish a clear causal connection between the proteinopathy of CTE and suicide. At present, however, there is insufficient scientific evidence to conclude that there is a strong causal relationship between the presence of these proteinopathies and suicide in former athletes. Additional research is needed to determine the extent to which the neuropathology of CTE is a possible mediator or moderator variable associated with suicide.